Changes In Retail Consumer Shopping Behavior After The End Of Covid 19 In Indonesia: Towards Digital Transformation Behavior - Idah Kusuma Dewi (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
This study aims to determine the changes in online shopping behavior of retail consumers after the end of covid 19 in Indonesia and the possibility of online shopping sustainability in the future towards digital transformation. Changes in consumer behavior occur due to the application of social distancing, including changes in the selection of retail product purchase locations and changes in transaction models to obtain the required retail products. The change of buying and selling locations and payment models from offline to online is inevitable. Therefore, Indonesian people are now increasingly accustomed to making purchases of various purposes online. Now, more and more people are making purchases online, so the impact on online stores is beginning to be seen with the increase in transaction activity. Research methods using previous research literature. The type of retail in this study is limited to the category of independent traditional retail stores such as food stalls, mini supermarkets, grocery stores and fashion stores as well as online shopping services that are still valid until the time of this study. Suggestions for consumers and businesses to continue to adjust online shopping behavior with the Times and technological sophistication towards digital transformation. In the future, online shopping is still needed because of the practical way with digital transformation service facilities that match consumer demands.